Effect of oxidative stress on ventricular repolarization in patients with type 2 diabetes: Non-invasive quantification via transmural dispersion of repolarization - Tokatlı, Alptuğ; Yi?iner, Ömer; Kılıçaslan, Fethi (Springer, 2016)
We read the article entitled ‘Increased serum gamma-glutamyltransferase levels are associated with ventricular instability in type 2 diabetes’ by Wang et al. with great interest [1]. In this article, it was focused on association between serum gamma glutamyltransferase (GGT) levels and ventricular instability in patients with type 2 diabetes mellitus (T2DM). In this well-designed research, they reported that increased serum GGT levels are associated with some markers of ventricular repolarization abnormalities in the early stage of T2DM.
WOS: 000376668100031
PubMed ID: 26553108
Keywords: Electrocardiography; Patients; Ventricular Repolarization